2020
DOI: 10.29252/iem.6.3.219
|View full text |Cite
|
Sign up to set email alerts
|

ELISA and Copan Based Evaluation and Analysis of Antibiotic Residues in Cattle Milk in Qazvin, Iran

Abstract: Daily consumption of milk containing antibiotic residues has become a great public health concern. This study aimed to evaluate the antibiotic residues in cattle raw milk using Copan milk test and specific enzyme-linked immunosorbent (ELISÁ) kits. Materials & Methods: In this study, 92 milk samples were collected from Qazvin province, Iran in two seasons during 2019. All the samples were analyzed by the Copan milk test and competitive ELISA kits to evaluate gentamicin, tetracycline, tylosin, chloramphenicol, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Chloramphenicol and nitrofuran residues in honey can be determined by the ELISA technique, and nitroimidazole residues by liquid chromatography coupled with mass spectrometry [57][58][59]. MRLs for nitrofurans and their metabolites analyzed from honey samples are established by the European Union through regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Chloramphenicol and nitrofuran residues in honey can be determined by the ELISA technique, and nitroimidazole residues by liquid chromatography coupled with mass spectrometry [57][58][59]. MRLs for nitrofurans and their metabolites analyzed from honey samples are established by the European Union through regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The present study also found that the quality of dairy production is inconsistent, as reflected in studies on quality. Some studies have reported concerns regarding chemical, biological, or physical safety risks, or a reduction in the quality of raw milk or dairy products [44][45][46][47][48][49]; other studies reported production aligning with standards [50][51][52][53]. The inconsistency in dairy production quality is not only related to factors such as season, climate, and production methods [54] but it is also influenced by the unstable macroeconomic situation, sectoral policies, and the monitoring system's structure.…”
Section: Discussionmentioning
confidence: 99%